2003
DOI: 10.1149/1.1554919
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Adsorption Isotherms of Overpotentially Deposited Hydrogen at Poly-Au and Rh/H[sub 2]SO[sub 4] Aqueous Electrolyte Interfaces

Abstract: The Langmuir adsorption isotherms of over-potentially deposited hydrogen ͑OPD H͒ for the cathodic hydrogen evolution reaction ͑HER͒ at poly-Au and Rh/0.5 M H 2 SO 4 aqueous electrolyte interfaces have been studied using cyclic voltammetric and ac impedance techniques. The behavior of the phase shift (0°р Ϫ р 90°) for the optimum intermediate frequency can be linearly related to that of the fractional surface coverage (1 у у 0) of OPD H for the cathodic HER at the interfaces. The phase-shift profile ͑Ϫ vs. E͒ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 33 publications
3
61
1
1
Order By: Relevance
“…13,21 Considering the rate determining Volmer reaction throughout the full range of cathodic currents, either as an ordinary charge transfer reaction or a barrierless reaction, the surface coverage of H ads is expected to be low (θ→0), as discussed in more detail in H + adsorption rate determining step section below. However, this was found to be in contrast with the findings from a study by Chun et al 6 where a significant coverage of H ads (θ→1) was reported in the 120 mV Tafel slope region.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…13,21 Considering the rate determining Volmer reaction throughout the full range of cathodic currents, either as an ordinary charge transfer reaction or a barrierless reaction, the surface coverage of H ads is expected to be low (θ→0), as discussed in more detail in H + adsorption rate determining step section below. However, this was found to be in contrast with the findings from a study by Chun et al 6 where a significant coverage of H ads (θ→1) was reported in the 120 mV Tafel slope region.…”
contrasting
confidence: 99%
“…6 Their measurements showed a low surface coverage at the low cathodic overpotentials, which was rapidly increased to full coverage at higher cathodic overpotentials. Based on these results, authors report the value of K = 2.3 × 10 −6 M −1 for the Langmuir equilibrium constant.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…8 show the four numerically calculated Langmuir adsorption isotherms of (H + D) corresponding to K = 5.3 × 10 , respectively. For 0.2 < θ < 0.8, all of the Langmuir adsorption isotherms are always parallel to each other [13,16,42]. Correspondingly, all of the slopes of the Langmuir adsorption isotherms, i.e.…”
Section: Correlation Constants Between the Adsorption Isothermsmentioning
confidence: 99%
“…Thus, the tedious experimental procedures presented there [e.g. 13,16,[19][20][21]27] have been used to verify or confirm the validity and correctness of the phase-shift method. This is discussed in more detail in the section on theoretical and experimental backgrounds of the phase-shift method.…”
Section: Introductionmentioning
confidence: 99%